Sports Financing: Analysis of Agreements signed in Municipalities of the State of São Paulo - Marco Aurelio Gonçalves Nobrega dos Santos; Elisabete dos Santos Freire (Universidade Salgado de Oliveira, 2020)
Among the main factors for the joint and collective construction of sports public policies that meet the real needs and interests of the population is the budget/financing, which is very precarious in the Brazilian municipalities and which mostly reflect in articulations and political interests, parliamentary amendments and dependence on state and federal government resources through the signing of agreements. The Secretariat of Sport, Leisure, and Youth is, at the state level, the entity in charge of promoting and directing actions related to public sports policies in the municipalities of São Paulo. The objective of our work was to verify the agreements signed by the state entity, which were signed with 12 municipalities of the Ourinhos micro-region and to analyze municipal budgets in the view of their managers. The data were collected from the portal of the Department of Finance and Planning of the state of São Paulo and interviews with managers. The results revealed that although agreements were contemplated, it falls short of the reality that we consider to be contradictory to the needs of these municipalities. Also, the lack of knowledge and lack of participation in the elaboration in the municipal budgets by the managers revealed limitations of technical procedures and processes that run into political, bureaucratic and formative aspects of planning, management, training and fundamentally, a scenario constituted by municipalities of economically with limitations of financial resources, in which the sport does not become a priority of investments and of public policies.